ZmDof30 Negatively Regulates the Promoter Activity of the Pollen-Specific Gene Zm908 - Peng, Jing; Qi, Xin; Chen, Xiyang; Li, Nan; Yu, Jingjuan (Frontiers in Plant Science, 2017)
The maize (Zea mays) pollen-predominant gene Zm908, a novel small-peptide gene, was reported to play critical roles in pollen germination and pollen tube growth in our previous work. In this study, we aimed to explore the regulatory mechanism of Zm908. The putative promoter of Zm908 was cloned and analyzed. The activity analysis of a series of promoter truncations in different tissues of transgenic tobacco plants indicated that the Zm908 promoter is pollen-specific and that the -126 to -68 region is crucial for pollen expression. The 5’deletion analysis of the -126 to -68 region revealed that the -126 to -102 region functions as a transcriptional suppression element. ZmDof30, which is predominantly expressed in pollen and whole anthers, was cloned and characterized. ZmDof30-GFP localized to the nuclei of maize protoplasts and possessed no transcriptional activation activity in a yeast system. ZmDof30 could bind to the AAAG elements in p184 sequence containing the -126 to +58 region of the Zm908 promoter in vitro and in vivo, and negatively regulated p184 activity in tobacco leaves. Collectively, ZmDof30 may function as a Zm908 transcriptional repressor in pollen, and these results may provide a better understanding of the regulation of the Zm908 gene. Additionally, the pollen-specific Zm908 promoter may be valuable for genetically engineering male sterility.